Assessing knowledge transfer for facility management to the development of new students' residential colleges in UTHM, Malaysia - Adeyemi, Ifeoluwa Adedoyin (2019)
Existing literature has revealed that ninety percent (90%) of the total funds allocated to universities by the government is spent on maintenance. Studies have revealed that the main reason for the high maintenance cost is due to building design decisions by architects with unrealistic expectation on how the buildings should operate. The architects are rarely present during building operation phase, and thus unaware of how design decisions affect building operation. Researchers agreed that to reduce maintenance cost, knowledge from building operation should be transferred to the design process. The best way to achieve this is by including the facility manager to every stage of the building development process. But despite the many benefits to be gained from the transfer of FM knowledge, it is rarely considered in the development of new buildings. This research looked to assess the transfer of FM knowledge to the development of new students' residential colleges in Universiti Tun Hussein Onn Malaysia (UTHM). The qualitative case study research design was used to fulfil the research purpose, and qualitative tools such as semi-structured interviews and focus groups were used to collect data for the research. Findings revealed that although the FM Division is well equipped to create, manage and share knowledge, the transfer of FM knowledge is gradually becoming a thing of the past as the knowledge transferred to the new students' residential colleges ranged from minimal to none. This was mainly because the new students' residential colleges were developed by private developers.